Perspectives of occupants with mobility impairments on evacuation methods for use during fire emergencies. (July 2017) - Butler, Kathryn; Kuligowski, Erica; Furman, Susanne; Peacock, Richard
Abstract: Since the tragic loss of life in the World Trade Center disaster, efforts have refocused on the provision of safe and efficient evacuation procedures, especially for occupants who cannot negotiate exit stairs without assistance. Several evacuation options have been designed specifically for people with mobility impairments, including occupant evacuation elevators (OEEs). Face-to-face interviews were conducted with 51 participants with mobility impairments working in buildings located in five major metropolitan areas within the U.S. The dual goals in this study were to gain an understanding of how building occupants with mobility impairments evacuate multi-story buildings during fire emergencies and to identify perspectives on the use of elevators during fire evacuations. Data analysis of interviews highlighted the benefits and concerns of study participants involving both typical building evacuation methods (i.e., emergency stair travel devices and areas of refuge), as well as evacuation methods using elevators. This study also highlights improvements that can be made to elevator systems, particularly OEEs, to reduce anxiety about fire evacuation and increase trust in the occupant evacuation elevator system via a variety of means, including education and consultation in preparation for the evacuation, information and attention to occupant needs while the evacuation is taking place, and two-way feedback and discussions afterwards. Key to all of these improvements is the need to include those with mobility impairments in the planning and execution of fire evacuations and to facilitate their ability for self-evacuation as much as is practicable. The results of this study led to guidance on evacuation planning and procedures, the use of existing elevators for evacuation of people with mobility impairments, and the use of occupant evacuation elevators. Highlights: Perspectives from people with mobility impairments on existing and future evacuation methods. Characteristics of beneficial evacuation strategies for people with mobility impairments. Areas where improvements can be made to evacuation planning and procedures.